Sosialisasi Literasi Ekonomi Syariah Bagi Masyarakat di Desa Tanjungsari Kecamatan Pondoksalam Purwakarta - Saepudin, Ahmad (STIE Syariah Indonesia Purwakarta, 2023)
The majority of rural communities at this time, according to the identity of the population data of Tanjungsari Village, are more dominated by Muslims, so all activities carried out on a daily basis should be in accordance with sharia. Seeing that there are still many community economic activities in Tanjungsari Village, Pondoksalam District, Purwakarta Regency which are not based on knowledge of sharia economics, in which some of them still carry out activities in ribawi, gharar and maisyir transactions and other transactions. So with this dedication it is considered important enough to socialize sharia economic literacy in the people of Tanjungsari Village, Pondoksalam District, Purwakarta Regency. This PKM program aims to provide an understanding of the Islamic economy for the community in Tanjungsari Village, Pondoksalam District, Purwakarta. This PKM method uses a lecture and discussion approach. PKM results on the socialization of